A novel integrated system for heavy metals removal and biodiesel production via green microalgae: A techno-economic feasibility assessment. Issue 6 (December 2022) - Hamed, Seham M.; El Shimi, Hassan I.; van Dijk, Jesper R.; Osman, Ahmed I.; Korany, Shereen Magdy; AbdElgawad, Hamada
Abstract: The removal of heavy metals combined with biodiesel production by microalgae in a cost-effective way is a promising approach. Herein, we grew two green microalgal species, Chlorella sorokiniana and Scenedesmus acuminatus, in media contaminated with Cu 2+ (3.2 ppm) or Zn 2+ (65.4 ppm) to investigate their growth and full metabolic profile. Furthermore, to integrate the potential economic impact of biodiesel production with heavy metals removal efficiencies. Although acute exposure to heavy metals, on the other hand, reduced growth and increased removal efficiencies of Cu 2+ (59.4, 98.1%) and Zn 2+ (72.4, 98.2%) in C. sorokiniana and S. acuminatus, respectively. Besides, Cu 2+ and Zn 2+ increased primary metabolites, particularly lipids (49, 47% in S. acuminatus, 27, 26% in C. sorokiniana ), with a significant induction in the unsaturation levels. Indicating that C. sorokiniana and S. acuminatus are excellent phycoremediators for industrial drainage and future sustainable algal-biofuels platform. Economic assessment of daily 1000-tonne biodiesel production from S. acuminatus grown on highly polluted wastewater via Na4 SiO4 transesterification catalysis has all been assessed with an accuracy of ± 10% for the price of the diesel of US 1000/tonne and for the cost of the evaluated algal biomass of US 430/tonne. The daily 1000 T algal diesel business was viable, with a return on high investment (16.4%) and a payback period of 5 years. According to break-even and sensitivity analyses, the algal diesel cost that makes this business viable should be greater than US 147/barrel, while the biomass cost should not exceed US 462/tonne. Brent Crude Oil Spot exceeds US 95/barrel indicating promising prospects for algal fuel industrialization. Furthermore, the protein and amino acids-based waste biomass may serve as a sustainable biorefienry platform for various biofuel industries through biomass conversion technologies. Graphical Abstract: ga1 Highlights: Scenedesmus acuminatus is a promising biomass-derived biodiesel feedstock. S. acuminatus experienced high Cu 2+ and Zn 2+ removal & lipid accumulation. Cu 2+ and Zn 2+ increased amino acids & unsaturated fatty acids in S. acuminatus. Techno-economic analysis of green-diesel project indicated 1000 T daily production rate. Diesel business using S. acuminatus is feasible when algae oil content ˃ 41.1% and BCO exceeds US 95/ barrel.